Gene expression of membrane transporters: Importance for prognosis and progression of ovarian carcinoma - Elsnerova, Katerina; Mohelnikova-Duchonova, Beatrice; Cerovska, Ela; Ehrlichova, Marie; Gut, Ivan; Rob, Lukas; Skapa, Petr; Hruda, Martin; Bartakova, Alena; Bouda, Jiri; Vodicka, Pavel; Soucek, Pavel; et al. (Oncology reports, 2016)
Membrane transporters (such as ABCs, SLCs and ATPases) act in carcinogenesis and chemoresistance development, but their relevance for prognosis of epithelial ovarian cancer (EOC) remains poorly understood. We evaluated the gene expression profile of 39 ABC and 12 SLC transporters and three ATPases in EOC tissues and addressed their putative role in prognosis and clinical course of EOC patients. Relative gene expression in a set of primary EOC (n=57) and in control ovarian tissues (n=14) was estimated and compared with clinical data and survival of patients. Obtained data were validated in an independent set of patients (n=60). Six ABCs and SLC22A18 gene were significantly overexpressed in carcinomas when compared with controls, while expression of 12 ABCs, five SLCs, ATP7A and ATP11B was decreased. Expression of ABCA12, ABCC3, ABCC6, ABCD3, ABCG1 and SLC22A5 was higher in high grade serous carcinoma compared with other subtypes. ABCA2 gene expression significantly associated with EOC grade in both sets of patients. Notably, expression level of ABCA9, ABCA10, ABCC9 and SLC16A14 significantly associated with progression-free survival (PFS) of the disease in either pilot or validation sets. ABCG2 level associated with PFS in the pooled set of patients. In conclusion, ABCA2, ABCA9, ABCA10, ABCC9, ABCG2 and SLC16A14 present novel putative markers of EOC progression and together with the revealed relationship between ABCA12, ABCC3, ABCC6, ABCD3, ABCG1 and SLC22A5 expression, and high grade serous type of EOC should be further examined by larger follow-up study.
Keywords: senioři; Membrane Transport Proteins; Reproducibility of Results; Gene Expression Profiling; Disease Progression; reprodukovatelnost výsledků; progrese nemoci; Prognosis; regulace genové exprese u nádorů; Middle Aged; nádory vaječníků; membránové transportní proteiny; Disease-Free Survival; ženské pohlaví; prognóza; Gene Expression; Humans; Gene Expression Regulation, Neoplastic; pilotní projekty; lidé středního věku; Pilot Projects; exprese genu; stanovení celkové genové exprese; Female; Aged; Ovarian Neoplasms; přežití bez známek nemoci; lidé